Decreased Plasma Maresin 1 Concentration Is Associated with Diabetic Foot Ulcer - Tian Miao; Bangliang Huang; Niexia He; Lihua Sun; Guangsheng Du; Xiaoli Gong; Yong Xu; Yi Zheng; Hongting Zheng; Hua Qu (Mediators of Inflammation)
Aims. To assess the maresin 1 (MaR1) contents in type 2 diabetic patients with or without diabetic foot ulcer and to analyze the association of MaR1 concentrations with several metabolism-related parameters. Methods. Plasma MaR1 concentrations were analyzed in 96 subjects with normal glucose tolerant (NC, n=43), type 2 diabetes (T2DM, n=40), or diabetic foot ulcer (DFU, n=13). The intravenous glucose tolerance test (IVGTT) and biochemical parameters were measured in all participants. Results. Plasma MaR1 concentrations were significant decreased in type 2 diabetes patient with or without DFU compared with NC (both P<0.001) and were lowest in DFU patients among these 3 groups. (DFU vs. T2DM, P<0.05). Plasma MaR1 concentrations were negatively correlated with BMI, waist circumference (Wc), waist hip ratio (WHR), systolic blood pressure (SBP), diastolic blood pressure (DBP), LDL-c, FPG, 2hPG, HbA1c, and homeostasis model assessment for insulin resistance (HOMA-IR) (all P<0.05) and were positively correlated with HDL-c, acute insulin response (AIR), area under the curve of the first-phase (0-10 min) insulin secretion (AUC), and homeostasis model assessment for beta-cell function (HOMA-β) (all P<0.05). After adjusting for age and sex, Wc, WHR, TG, FPG, 2hPG, HbA1c, HOMA-IR, AIR, AUC, and HOMA-β remain statistically significant (all P<0.05). Conclusions. Plasma MaR1 concentration were decreased in T2DM with or without DFUs and were the lowest in DFU patients. The decreased plasma MaR1 strongly associated with obesity, impaired glucose and lipid metabolism, reduced first-phase of glucose-stimulated insulin secretion, and enhanced insulin resistance.